STRATEGIC MANAGEMENT OF AGRICULTURAL ENTERPRISES CONSIDERING MARKETING RISKS - Bochko , O. Yu.; Zarichna , O. V.; Kubrak , N. R. (The actual problems of regional economy development, 2024)
The regional aspects of strategic management of agriculture (farming) have been studied, taking into account marketing risks. These aspects play a crucial role in ensuring effective and sustainable development of the agricultural industry, especially in the context of dynamic changes in market and climatic factors, which calls for further research. The purpose of the article is to discuss and analyze regional aspects of strategic management of agriculture, considering marketing risks. To achieve this goal, a marketing risk assessment technique was applied. The authors used inductive and deductive methods for analyzing marketing risks while writing the article. Through analysis and comparison, a method for comparing the assessment of marketing risks was implemented. The abstract-logical method was employed for theoretical generalizations and forming conclusions. The methods of evaluating marketing risks are substantiated. Product sales channels are discussed and systematized, taking into account marketing risks.To reduce the level of marketing risks, it is advisable to: Identify areas of increased risk and their degree, then make decisions to mitigate them or prevent the risks entirely. Preserve and transfer risks as needed. Reduce the level of risk.Thorough analysis and customer testing and experiments are proposed. The authors emphasize the importance of utilizing various marketing channels, such as social networks, search advertising, electronic marketing, and others. A backup plan is proposed in case of unforeseen circumstances or unsuccessful outcomes. The development of innovative directions, processes for stimulating and training the marketing team in new technologies and strategies, and encouraging cooperation with other companies or organizations are all suggested. Additionally, reducing marketing risks involves motivation. Prospects for further research in this area include a detailed study of macro-, meso-, and micro-environmental factors that affect the activity of agricultural enterprises.